2006
DOI: 10.1007/s10029-005-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial-dependent MMP-2 expression in fibroblasts from patients with recurrent incisional hernias

Abstract: With regard to the pathogenesis of recurrent incisional hernia, an impaired connective tissue quality leading to an aberrant scarring process has been proposed. For the matrix metalloproteinase (MMP-2) a pathogenetic involvement in direct inguinal hernia development is reported. With mesh implantation as the gold standard treatment for incisional hernias, the aim of the present study was to investigate the MMP-2 expression in patients with recurrent incisional hernias with and without mesh-materials. In primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
1
27
1
1
Order By: Relevance
“…It is suggested that the inflammatory mesh response is an underlying pathophysiological mechanism for chronic pain after mesh implantation [36]. Biomaterial implantation frequently induces a chronic wound that is characterized by activation of matrix metalloproteinases (MMPs) [26,37]. MMPs constitute a family of enzymes that degrade extracellular matrix components [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the inflammatory mesh response is an underlying pathophysiological mechanism for chronic pain after mesh implantation [36]. Biomaterial implantation frequently induces a chronic wound that is characterized by activation of matrix metalloproteinases (MMPs) [26,37]. MMPs constitute a family of enzymes that degrade extracellular matrix components [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas MMP-2 expression is necessary for a proper wound healing, high levels of MMP-2 are associated with chronic inflammatory processes such as arthritis or foreign body reaction [26]. Advanced investigations by Jansen et al revealed that mesh implantation mediates enhanced MMP-2 gene transcription with concomitantly up-regulated MMP-2 protein synthesis and enzymatic activity [27].…”
Section: Introductionmentioning
confidence: 98%
“…A fourth study found no difference in the MMP-1 level in the fascia transversalis of patients with an incisional hernia compared with controls, but the MMP-2 level was significantly increased 63 . A final study found no difference in the MMP-2 level in skin fibroblasts of patients with a recurrent incisional hernia compared with controls 74 . More research is needed on MMP activity in incisional hernia before conclusions can be drawn.…”
Section: Studies On Collagen Metabolism In Incisional Herniamentioning
confidence: 98%
“…They are particularly important in the regulation of growth and apoptotic processes [21, 22]. There appears to be significant overexpression of MMP-2 in incisional hernia [23]. Since collagen synthesis can be suppressed by inflammatory processes, such as postoperative sepsis, the functionality of the various MMP and collagens may be impaired by the wound milieu [24].…”
Section: Discussionmentioning
confidence: 99%